The Architecture of the Southern Puna Magmatic System: Integrating Seismic and Petrologic Observations With Geochemical Modeling. Issue 7 (7th July 2021) - Delph, Jonathan R.; Shimizu, Kei; Ratschbacher, Barbara C.
Abstract: Improvements in geochemical, petrologic, and geophysical methods and data have led to a paradigm‐shift in understanding magmatic system architecture away from isolated magmatic chambers toward transcrustal "mushy" magmatic systems. Geochemical and petrologic studies indicate that magma storage and differentiation occurs over a range of depths throughout the crust, while geophysical techniques delineate in situ spatial distributions of melt at similar scales. However, seismic properties are nonunique with respect to composition and melt percentage, and must be integrated with geochemical observations to better understand the architecture and chemical evolution of magmatic systems. The southern Puna Plateau represents a locality where extensive geochemical and seismic data can be combined to investigate the role of depth‐dependent processes in generating compositionally diverse volcanism. By combining geochemical modeling with seismic images of shear‐wave velocity and attenuation, we find that magma storage and differentiation occurs predominantly at two depth ranges: (a) near the base of the crust (>40 km), where shear‐wave velocities are anomalously slow compared to what is expected (<4.0 km/s) and geochemical signatures indicate fractional crystallization and crustal assimilation in the garnet stability field, and (b) in the mid‐crust (∼20 km) beneath the Cerro Galan Caldera, where shear‐wave velocities necessitate the presence of melt (∼2.7 km/s) and europium (Eu) anomalies indicate low‐pressure differentiation. These geochemical and seismic results provide evidence for multi‐level melt evolution and are consistent with petrological features of exposed arcs, whose transcrustal architecture is characterized by discrete and compositionally evolved intrusive bodies in the mid‐crust and a compositionally heterogeneous lower crust. Plain Language Summary: The inferred architecture of the magmatic plumbing beneath volcanoes can vary widely depending on the discipline and/or methodology used to investigate them. Recent studies have worked to integrate these different perspectives into a holistic model, but this has proven difficult as some data sets provide very different information than others. In this study, we outline the apparently contrasting viewpoints of magma system architecture based on the geophysical and geochemical characteristics of active magmatic systems, and field studies of exposed and extinct magmatic systems. We then investigate a region in the central Andes of South America with good seismic data coverage and compositionally diverse volcanics that has erupted over a relatively small area in the last ∼8 Ma. These data sets reveal evidence for melt stagnation and evolution at two main locations: near the crust‐mantle transition and in mid‐crustal magma reservoirs. Contextualizing these results with the apparently continuous magmatic structure seen in exposed sections indicates that these contrasting perspectives can be reconciled by understanding the sensitivities and limitations of the individual data sets. Thus, the evidence that has led to the discrete conceptualizations of magma systems often inferred from seismic data or geochemistry are consistent with more‐or‐less continuous magmatic systems throughout the crust. Key Points: We integrate geophysical and geochemical results to understand the architecture of a continental arc system Magmas stagnate and differentiate predominantly at two depths: at or near the crust‐mantle transition (melting, assimilation, storage, and homogenization zone) and in the mid‐crust The discrete nature of magmatic systems from geochemistry and seismology are reconcilable with the transcrustal petrology of exposed arcs